Revitalizing Divine Values Through the Koran Reliance Ramadhan Program for SMKN 1 Palopo City Students - Ilyas, Ilyas; Seriyanti, Seriyanti (PT FORMOSA CENDEKIA GLOBAL, 2024)
One of the important pillars in education is the value of divinity, with the aim that students' morals and character can be formed. For this reason, in order for divine values to remain relevant, systematic and continuous efforts are needed. The month of Ramadan is the right time to increase religious values. One of the ways SMKN 1 Palopo City started the Ramadan Mainstay Mengaji Program is with the aim of improving the quality of Qur'an reading, and forming a more religious and noble character with a comprehensive method. The purpose of this service is to increase the understanding and practice of divine values among students. The program also aims to create an environment in the school that is more supportive of students' spiritual development, so that they can become people who are not only intellectually intelligent but also spiritually strong.